Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation